Sulfide-based solid electrolyte powder, method for producing sulfide-based solid electrolyte powder, sulfide-based solid electrolyte layer, and lithium-ion secondary battery
By developing sulfide solid electrolyte powder that emits light in the wavelength range of 660-750nm, and adding chromium source and oxygen source to form a chromium oxide film during the grinding process, the high reactivity and water sensitivity of sulfide solid electrolyte on the high-voltage cathode electrode is solved, and excellent electrochemical stability and water resistance are achieved.
Patent Information
- Application Number
- JP2024013092
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2024-01-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-05-26
AI Technical Summary
The existing sulfide solid electrolytes have high reactivity on high-voltage cathode electrodes, resulting in narrow theoretical potential windows and poor electrochemical stability. At the same time, they are sensitive to water, and produce hydrosulfides, resulting in poor water resistance.
A sulfide solid electrolyte powder was developed that emits light luminescence light in the wavelength range of 660-750nm, and the light luminescence peak ratio detected by Raman spectroscopy reaches 0.2 or above, including aluminum irodite crystals, and chromium sources and oxygen sources are added during the research and development process to form a chromium oxide film to improve electrochemical stability and water resistance.
It realizes excellent electrochemical stability and water resistance of sulfide solid electrolyte powder, and is suitable for lithium-ion secondary batteries.
Smart Images

Figure 0007658478000002 
Figure 0007658478000003 
Figure 0007658478000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a sulfide-based solid electrolyte powder, a method for producing a sulfide-based solid electrolyte powder, a sulfide-based solid electrolyte layer, and a lithium ion secondary battery. [Background technology]
[0002] Lithium ion secondary batteries are widely used in portable electronic devices such as mobile phones and notebook computers. Conventionally, liquid electrolytes have been used in lithium ion secondary batteries. On the other hand, in recent years, all-solid-state lithium ion secondary batteries that use solid electrolytes as the electrolyte of lithium ion secondary batteries have been attracting attention because of the expected benefits of improved safety, high-speed charging and discharging, and smaller casings.
[0003] Solid electrolytes are broadly divided into sulfide-based solid electrolytes and oxide-based solid electrolytes. Among them, sulfide-based solid electrolytes show high ionic conductivity because they contain sulfide ions with high polarizability. Examples of sulfide-based solid electrolytes include Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 Argyrodite-type crystals such as Li7P3S 11 Crystallized glass such as LPS crystallized glass is known. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2016-24874 [Non-patent literature]
[0005] [Non-Patent Document 1] Interface Stability in Solid-State Batteries,Chem.Mater.2016,28,266-273 Summary of the Invention [Problem to be solved by the invention]
[0006] On the other hand, sulfide-based solid electrolytes are known to have a narrow theoretical potential window and poor electrochemical stability due to their particularly high reactivity with high-voltage cathodes (Non-Patent Document 1).In addition, sulfide-based solid electrolytes react with moisture to generate hydrogen sulfide, resulting in a problem of poor water resistance (Patent Document 1).
[0007] In view of the above circumstances, an object of the present invention is to provide a sulfide-based solid electrolyte powder having excellent electrochemical stability and water resistance, a method for producing the sulfide-based solid electrolyte powder, a sulfide-based solid electrolyte layer, and a lithium-ion secondary battery. [Means for solving the problem]
[0008] As a result of extensive investigations, the present inventors have found that a sulfide-based solid electrolyte powder that emits photoluminescence light in a specific wavelength region is excellent in electrochemical stability and water resistance, and have thus completed the present invention.
[0009] That is, the present invention relates to the following [1] to
[10] . [1] A sulfide-based solid electrolyte powder that emits photoluminescence light with wavelengths between 660 and 750 nm. [2] The sulfide-based solid electrolyte powder according to [1], which has a photoluminescence peak ratio of 0.2 or more in a Raman spectrum obtained by excitation with light having a wavelength of 532 nm, as shown in the following formula: Photoluminescence peak ratio = Raman shift 4300 cm -1 ~4500cm -1 Integrated intensity of peaks in the region / Raman shift 400~450cm -1 Integrated intensity of peaks in the region [3] The sulfide-based solid electrolyte powder according to [1], which contains argyrodite-type crystals. [4] The sulfide-based solid electrolyte powder according to [1], having a lattice distortion of 0.002 or more. [5] The sulfide-based solid electrolyte powder according to [1], which satisfies the following formula: BET specific surface area (m 2 / g) × lattice distortion ≧ 0.01 [6] The sulfide-based solid electrolyte powder according to [1], wherein the atomic ratio of Cl element to Br element is 0.2:1.6 to 1.6:0.2. [7] A method for producing the sulfide-based solid electrolyte powder according to any one of [1] to [6]. [8] A method for producing a sulfide-based solid electrolyte powder according to [7], comprising a step of pulverizing a sulfide-based solid electrolyte containing at least one of a crystalline phase and an amorphous phase in the presence of a chromium source and an oxygen source. [9] A sulfide-based solid electrolyte layer comprising the sulfide-based solid electrolyte powder according to any one of [1] to [6].
[10] A lithium ion secondary battery comprising the sulfide-based solid electrolyte powder according to any one of [1] to [6]. Effect of the Invention
[0010] According to the present invention, it is possible to provide a sulfide-based solid electrolyte powder, a sulfide-based solid electrolyte layer, and a lithium-ion secondary battery that are excellent in electrochemical stability and water resistance. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a Raman spectrum showing the integrated intensity of the peak in the Raman shift region of 4300 cm −1 to 4500 cm −1 of the sulfide-based solid electrolyte powder of Example 3. [Diagram 2] FIG. 2 is a Raman spectrum showing the integrated intensity of the peak in the Raman shift region of 400 cm −1 to 450 cm −1 of the sulfide-based solid electrolyte powder of Example 3. [Diagram 3] FIG. 3 shows Raman spectra of the sulfide-based solid electrolyte powders of Examples 1, 3, and 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified as desired without departing from the gist of the present invention. In addition, the symbol "to" indicating a numerical range is used to mean that the numerical values before and after the symbol are included as the lower and upper limits.
[0013] <Sulfide solid electrolyte powder> The sulfide-based solid electrolyte powder according to an embodiment of the present invention (hereinafter, also referred to as the present powder) is characterized in that it emits photoluminescence light with a wavelength of 660 to 750 nm. The sulfide-based solid electrolyte powder that emits photoluminescence light in the above specific wavelength range has excellent electrochemical stability and water resistance.
[0014] In this embodiment, photoluminescence light having a wavelength of 660 to 750 nm is detected using a microscopic Raman spectrometer. The wavelength of the photoluminescence light varies somewhat depending on the state of the luminescence center. When photoluminescence light having a wavelength of 689.8 to 699.4 nm is emitted, the Raman shift in the Raman spectrum obtained by exciting with light having a wavelength of 532 nm is 4300 to 4500 cm. -1 This means that the Raman shift has a peak in the region of 0.01 to 0.05, because the definition of the Raman shift is the difference between the energy of the incident excitation light and the energy of the observed Raman scattered light.
[0015] The Raman spectrum is measured using a microscopic Raman spectrometer (e.g., LabRAM HR Evolution, manufactured by Horiba, Ltd.). The measurement conditions are an objective lens with a magnification of 10 and a numerical aperture of 0.25, and the power of the laser focused on the sulfide-based solid electrolyte powder is adjusted to about 5 mW. The intensity of the obtained spectrum is calibrated using a standard halogen lamp light source. Note that the above-mentioned "having a peak" generally means having a value three times or more the standard deviation value of the background (a sample that does not emit light).
[0016] In this embodiment, photoluminescence light is emitted in the wavelength range of 660 to 750 nm because Cr corresponding to the above peak is present on the particle surface of the sulfide-based solid electrolyte powder. 3+ The photoluminescence light with wavelengths of 660 to 750 nm is due to the presence of Cr 3+ It originates from the 2E → 4A2 spin-forbidden transition of . Its wavelength is known to be 692 and 694 nm (see, for example, Michele et al., Chem. Mater. 2021, 33, 9, 3379-3385).
[0017] Thus, this powder has Cr on the particle surface. 3+ Due to the presence of Cr on the surface of the particles, the powder emits photoluminescence light with a wavelength of 660 to 750 nm, and due to this property, the powder exhibits excellent electrochemical stability and water resistance. 3+ Due to the presence of these elements, when the powder exhibits excellent electrochemical stability and water resistance, the photoluminescence light is emitted in the wavelength range of 660 to 750 nm.
[0018] The surface of the powder particles is coated with Cr. 3+ Although the reason why the presence of Cr can realize excellent electrochemical stability and water resistance is not clear, it is presumed as follows. 3+ It is presumed that the oxidative decomposition of the powder is suppressed and the electrochemical stability is increased by the incorporation of chromium into the crystal structure of the solid electrolyte, or by the formation of a distorted chromium oxide film on the particle surface, and further, the surface reaction with HO is suppressed and the water resistance is improved. Note that the present embodiment is not limited to the above-mentioned mechanism of action.
[0019] The powder preferably has a photoluminescence peak ratio of 0.2 or more in a Raman spectrum obtained by exciting the powder with light having a wavelength of 532 nm, as shown in the following formula: Photoluminescence peak ratio = Raman shift 4300 cm -1 ~4500cm -1Integrated intensity of peaks in the region / Raman shift 400~450cm -1 Integrated intensity of peaks in the region
[0020] Raman shift 4300cm -1 ~4500cm -1 The integrated intensity of the peak in the region refers to the integrated intensity of the peak indicated by the arrow A in the Raman spectrum obtained by exciting with light of a wavelength of 532 nm as shown in Figures 1 and 3. This is because, as described above, Cr 3+ This is due to the presence of Raman shifts of 400 to 450 cm -1 The integrated intensity of the peak in the region refers to the integrated intensity of the peak indicated by arrow B in Figures 2 and 3. This is because the powder contains PS4 3- This is due to the presence of a structure derived from
[0021] The photoluminescence peak ratio of 0.2 or more corresponds to a Raman shift of 4300 to 4500 cm -1 The peak in the region is high, which means that Cr is present on the surface of the particles of this powder. 3+ exists and its Cr 3+ This existence form of the particles means that the particles have a structure that allows them to exhibit excellent electrochemical stability and water resistance.
[0022] The photoluminescence peak ratio in the present powder is more preferably 0.3 or more, even more preferably 0.5 or more, and particularly preferably 0.75 or more. Although there is no particular upper limit, as a practical range, the photoluminescence peak ratio is more preferably 10 or less, even more preferably 5 or less, and particularly preferably 3 or less.
[0023] This powder has Cr on its particle surface. 3+ The lattice distortion of the present powder is preferably 0.002 or more, more preferably 0.003 or more, and even more preferably 0.0035 or more. The lattice distortion of 0.002 or more indicates that Cr is present on the particle surface of the present powder. 3+ exists and its Cr 3+This existence form of the particles means that the particles have a structure that allows them to exhibit excellent electrochemical stability and water resistance.
[0024] From the viewpoint of ion conductivity, the lattice distortion in the present powder is preferably 0.01 or less, more preferably 0.007 or less, and even more preferably 0.005 or less.
[0025] The lattice distortion of the powder is measured by carrying out Rietveld analysis of the XRD pattern, as described later in the Examples.
[0026] This powder has a BET specific surface area of 5m 2 / g or more is preferable, and 9m 2 / g or more is more preferable, and 12m 2 When the BET specific surface area of the powder is within the above range, Cr is formed on the particle surface of the powder. 3+ can be efficiently incorporated.
[0027] In addition, since it becomes difficult to handle the powder if its specific surface area becomes too large, the BET specific surface area of this powder is set at 30 m 2 / g or less is preferable, and 25m 2 / g or less is more preferable, and 20m 2 / g or less is more preferable.
[0028] Here, the BET specific surface area means the nitrogen adsorption specific surface area measured by the BET method. The measurement of the BET specific surface area of the present powder is carried out, for example, according to the conditions described in the Examples.
[0029] This powder has a BET specific surface area and Cr 3+ The BET specific surface area (m2) is an index obtained by multiplying the lattice distortion, which is the effect of the incorporation of ions into the surface, by the lattice distortion. 2 / g)×lattice strain” is preferably 0.01 or more, more preferably 0.03 or more, and even more preferably 0.05 or more. 2Although there is no particular upper limit for "(x / g)×lattice strain," a realistic range may be, for example, 0.1 or less, 0.08 or less, or 0.07 or less.
[0030] The sulfide-based solid electrolyte in the present powder includes a sulfide-based solid electrolyte containing lithium element, for example, Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 , Li6PS5Cl, and Li 5.4 P.S. 4.4 Cl 1.6 sulfide-based solid electrolytes having an argyrodite-type crystal structure, such as Li-PS-Ha-based (Ha represents at least one element selected from halogen elements) crystallized glass, Li7P3S 11 Glass-ceramics containing Li-PS elements such as Li 10 GeP2S 12 and sulfide-based solid electrolytes having an LGPS type crystal structure such as those mentioned above.
[0031] The sulfide-based solid electrolyte may be a sulfide-based solid electrolyte containing an amorphous phase, a sulfide-based solid electrolyte containing a specific crystalline phase, or a sulfide-based solid electrolyte containing a crystalline phase and an amorphous phase, depending on the purpose. 3+ From the viewpoint of easiness of forming a distorted structure in which Li is incorporated into the particle surface, a sulfide-based solid electrolyte containing both a crystalline phase and an amorphous phase is preferable. Examples of sulfide-based solid electrolytes that tend to have such a structure include sulfide-based solid electrolytes having an argyrodite-type crystal structure and sulfide-based solid electrolytes such as crystallized glass containing Li-PS elements. From the viewpoint of lithium ion conductivity, the argyrodite-type crystal phase is more preferable. Also, from the first-principles calculation of solid electrolytes, Cr 3+ Since it is known that Ha is likely to exist around halogen anions, a sulfide-based solid electrolyte containing Ha is preferred from the viewpoint of improving water resistance and electrochemical stability.
[0032] As a sulfide-based solid electrolyte having excellent lithium ion conductivity, there can be mentioned a sulfide-based solid electrolyte having an argyrodite type crystal structure, among which a sulfide-based solid electrolyte having an element of Li-PS-Ha is preferable, and more preferably has a crystalline phase. In addition, such a halogen element is preferably derived from one or more selected from the group consisting of lithium chloride, lithium bromide, and lithium iodide. Furthermore, from the viewpoint of lithium ion conductivity, it is preferable that two or more are contained.
[0033] In the present powder, the atomic ratio of Cl element to Br element is preferably 0.2:1.6 to 1.6:0.2. By being in the above range, the ion conductivity is high. The above atomic ratio in the present powder is more preferably 0.4:1.4 to 1.4:0.4, and further preferably 0.6:1.2 to 1.2:0.6.
[0034] As described above, the sulfide-based solid electrolyte powder in this embodiment has Cr on its particle surface. 3+ It is preferable that the metal is present. This allows for excellent electrochemical stability and water resistance. In addition, if the metal is a trivalent transition metal, Cr 3+ It is believed that a similar effect can be achieved.
[0035] The lithium ion conductivity of this powder is 1.0×10 in order to improve the battery characteristics when used in a lithium ion secondary battery. -4 S / cm or more is preferable, and 5.0×10 -4 S / cm or more is preferable, and 1.0×10 -3 More preferably, 2.5×10 S / cm or more. -3 S / cm or more is particularly preferred.
[0036] The lithium ion conductivity is measured using an AC impedance measuring device (for example, potentiostat / galvanostat VSP manufactured by Bio-Logic Sciences Instruments) under the measurement conditions of measurement frequency: 100 Hz to 1 MHz, measurement voltage: 100 mV, and measurement temperature: 25°C.
[0037] <Sulfide solid electrolyte layer> When the powder is used in a lithium ion secondary battery, it forms a sulfide-based solid electrolyte layer (hereinafter, simply referred to as a solid electrolyte layer) together with other components such as a binder, if necessary. Conventionally known binders and other components are used.
[0038] The content of the present powder in the entire solid electrolyte layer is preferably 80 mass % or more, and more preferably 90 mass % or more.
[0039] The solid electrolyte layer can be formed by a conventional method. For example, the components constituting the solid electrolyte layer are dispersed or dissolved in a solvent to form a slurry, which is then coated in a layer (sheet), dried, and optionally pressed to form the solid electrolyte layer. If necessary, the binder may be removed by applying heat. The thickness of the solid electrolyte layer can be easily adjusted by adjusting the coating amount of the slurry, etc.
[0040] Also, instead of wet molding, the solid electrolyte layer may be formed by dry press molding of the powder or the like on the surface of a positive electrode or a negative electrode, etc. Alternatively, the solid electrolyte layer may be formed on another substrate, and then transferred onto the surface of a positive electrode or a negative electrode, etc.
[0041] The powder may be mixed with a positive electrode active material or a negative electrode active material to be used as a positive electrode layer or a negative electrode layer. The positive electrode active material or negative electrode active material, current collector, binder, conductive assistant, etc. used in the positive electrode layer or negative electrode layer may be any of the conventionally known materials.
[0042] <Lithium-ion secondary battery> The lithium ion secondary battery in which the present powder is used may be any battery containing the present powder, and may include, for example, the above-mentioned solid electrolyte layer, a positive electrode layer, and a negative electrode layer.
[0043] The material of the exterior body of the lithium ion secondary battery may be a conventionally known one. The shape of the lithium ion secondary battery may be a conventionally known one, for example, a coin type, a sheet type (film type), a folded type, a wound type, a bottomed cylindrical type, a button type, etc., and may be appropriately selected depending on the application.
[0044] <Method of manufacturing sulfide-based solid electrolyte powder> The method for producing the present powder is described below, but the present powder is not limited to those produced by this method. The method for producing the present powder includes, for example, the following steps 1 and 2. (Step 1) Obtaining a sulfide-based solid electrolyte containing at least one of a crystalline phase and an amorphous phase (Step 2) Crushing the sulfide-based solid electrolyte obtained in step 1 into powder. Steps 1 and 2 will be explained below in order.
[0045] (Process 1) A conventionally known method can be applied to the step of obtaining a sulfide-based solid electrolyte containing at least one of a crystalline phase and an amorphous phase. For example, it is preferable to include a step of obtaining a raw material mixture, a step of reacting the raw material mixture, and a step of crystallizing or amorphizing. The step of reacting the raw material mixture may be a heating reaction or a mechanochemical reaction. The raw material mixture may be heated to crystallize or amorphize the sulfide-based solid electrolyte, in which case a separate step of crystallizing or amorphizing may not be included. In addition to the step of obtaining a crystalline phase or an amorphous phase, a step of increasing the crystallinity or a step of rearranging crystals may also be included.
[0046] The raw materials vary depending on the composition of the desired crystalline or amorphous phase, but may be, for example, raw materials containing Li, P, and S. When it is desired to obtain an argyrodite-type crystalline phase containing Ha or an LPSHa-type crystallized glass containing Ha, raw materials containing Ha in addition to Li, P, and S may be used.
[0047] Specifically, for example, to obtain argyrodite-type crystals, raw materials containing Li, P, S, and Ha are used. Also, for example, in the case of LPS crystallized glass, raw materials containing Li, P, and S are used. These may be materials for obtaining argyrodite-type crystals containing Li, P, S, and Ha, or materials conventionally known as LPS crystallized glass containing Li, P, and S.
[0048] In the case of argyrodite type crystals, for example, a mixture of a compound containing Li (lithium), a compound containing P (phosphorus), a compound containing S (sulfur), and a compound containing Ha (halogen) can be mentioned. In the case of LPS crystallized glass, for example, a mixture of a compound containing Li (lithium), a compound containing P (phosphorus), and a compound containing S (sulfur) can be mentioned.
[0049] Examples of compounds containing Li include lithium compounds such as lithium sulfide (Li2S), lithium oxide (Li2O), lithium carbonate (Li2CO3), lithium hydroxide (LiOH), and lithium sulfate (Li2SO4), as well as elemental lithium metal.
[0050] Examples of compounds containing P include phosphorus sulfides such as diphosphorus trisulfide (P2S3) and diphosphorus pentasulfide (P2S5), phosphorus compounds such as lithium phosphate (LiPO3, Li4P2O7, Li3PO4) and sodium phosphate (NaPO3, Na4P2O7, Na3PO4), and elemental phosphorus.
[0051] Examples of compounds containing S include the above-mentioned lithium sulfide (Li2S), the above-mentioned phosphorus sulfides (P2S3, P2S5), and hydrogen sulfide (H2S), and elemental sulfur can also be used.
[0052] Among the compounds containing Ha, examples of compounds containing Cl (chlorine) include lithium chloride (LiCl), phosphorus trichloride (PCl3), phosphorus pentachloride (PCl5), diphosphorus tetrachloride (P2Cl4), phosphoryl chloride (POCl3), sulfur dichloride (SCl2), disulfur dichloride (S2Cl2), sodium chloride (NaCl), and boron trichloride (BCl3).
[0053] Among compounds containing Ha, compounds containing Br (bromine) include, for example, lithium bromide (LiBr), phosphorus tribromide (PBr3), phosphoryl chloride (POBr3), disulfur dibromide (S2Br2), sodium bromide (NaBr), and boron tribromide (BBr3).
[0054] Among these, a combination of lithium sulfide, phosphorus sulfide, and at least one of lithium chloride and lithium bromide is preferred.
[0055] Some raw materials are very unstable in the air and may react with water to decompose, generating hydrogen sulfide gas or oxidizing. In such cases, it is preferable to mix them in an inert atmosphere. If no raw materials that are unstable in the air are used, mixing may be performed in the air.
[0056] The raw materials can be mixed by, for example, a mixer mill, a pin mill, a powder agitator, a media-less mixer such as airflow mixing, etc. The raw materials may be partially made amorphous by mixing before heating.
[0057] The raw material mixture can be crystallized or made amorphous by heating and melting it and then cooling it. Alternatively, the raw material mixture may be crystallized or made amorphous by heating it or by carrying out a mechanochemical reaction.
[0058] When raw materials are heated and melted and then cooled to crystallize or amorphize them, the state of the crystalline or amorphous phase can be adjusted by changing the cooling conditions, such as the cooling rate and pressure during cooling.
[0059] The heat melting conditions may be those known in the art. For example, the heating temperature is preferably 600 to 900°C. The heat melting time is preferably 0.1 to 10 hours. The pressure during heat melting is preferably normal pressure to slight pressure. The dew point during heat melting is preferably -20°C or lower, and although there is no particular lower limit, it is usually about -80°C. The oxygen concentration is preferably 1000 ppm or lower.
[0060] The heated and melted raw material mixture may be crystallized by, for example, quenching it at a cooling rate of 1° C. / sec or more under normal pressure. Alternatively, a stabilization treatment may be performed thereafter by further heat treatment. Alternatively, the material may be quenched to an amorphous state and used as is. Alternatively, the material may be crystallized by heating the amorphous material again.
[0061] When the raw material mixture is heated to crystallize or amorphize it, the heating conditions can be the same as those of the conventional process. For example, the heating atmosphere can be an inert gas atmosphere, a hydrogen sulfide gas atmosphere, a sulfur gas atmosphere, or a vacuum sealed tube. The heating temperature is preferably 200°C or higher and lower than 900°C. The heating time is preferably 0.1 to 100 hours. Heating may be performed multiple times.
[0062] (Process 2) Step 2 is a step of pulverizing the sulfide-based solid electrolyte containing at least one of a crystalline phase and an amorphous phase obtained in step 1 to obtain a powder.
[0063] In this step, it is preferable to pulverize the crystalline phase or amorphous phase in the presence of a chromium source such as Cr2O3. As a pulverization method, for example, a wet pulverization method can be used. In this step, Cr is formed on the particle surface of the obtained powder. 3+ As a result, excellent electrochemical stability and water resistance can be achieved.
[0064] The chromium source may be, for example, Cr2O3, Cr 3+ Organic solvents containing Cr 3+ Examples of the oxides include oxides containing ZnO and oxide coatings of SUS-based metals.
[0065] The chromium source is preferably added in an amount of 1 mass ppm or more, more preferably 10 mass ppm or more, and even more preferably 30 mass ppm or more, calculated as Cr, to the crystal phase or amorphous phase of the sulfide-based solid electrolyte. By adding the chromium source in an amount of 1 mass ppm or more, calculated as Cr, Cr is formed on the particle surfaces of the obtained powder. 3+ is present in an appropriate amount, and thus superior electrochemical stability and water resistance can be realized.
[0066] The chromium source may be contained to an extent that does not inhibit the ionic conductivity of the electrolyte. For example, the chromium source is preferably added in an amount of 5 mass % or less, more preferably 1 mass % or less, and even more preferably 0.1 mass % or less, calculated as Cr, to the crystalline phase or amorphous phase.
[0067] The amount of Cr in the chromium source can be calculated by ICP emission spectrometry.
[0068] In step 2, the crystalline phase or amorphous phase is preferably pulverized in the presence of an oxygen source. 3+ The oxygen source may be atmospheric oxygen, residual oxygen in a solvent, or a solvent containing oxygen such as ether.
[0069] The amount of oxygen taken into the electrolyte from the oxygen source is preferably 10 mass ppm or more, more preferably 100 mass ppm or more, and even more preferably 300 mass ppm or more, calculated as O, relative to the crystalline phase or amorphous phase of the sulfide-based solid electrolyte. 3+ This contributes to realizing a preferred existence form of the compound, and furthermore, excellent electrochemical stability and water resistance can be realized.
[0070] In addition, since there is no problem in containing oxygen atoms to the extent that they do not inhibit the ionic conductivity of the electrolyte, the amount of oxygen introduced into the electrolyte from the oxygen source is, for example, preferably 20 mass % or less, more preferably 5 mass % or less, and even more preferably 1 mass % or less, calculated as O, relative to the crystalline phase or amorphous phase.
[0071] The amount of oxygen taken up into the electrolyte from the oxygen source can be determined using an oxygen / nitrogen / hydrogen analyzer (eg, ONH836, manufactured by LECO).
[0072] The amount of oxygen in the oxygen source can be measured with an oxygen concentration meter (e.g., Model 201RS, manufactured by Techne Measurement Co., Ltd.) in the case of atmospheric oxygen, with an oxygen / nitrogen / hydrogen analyzer (e.g., ONH836, manufactured by LECO Co., Ltd.) in the case of oxygen derived from inorganic substances, with a DO meter (e.g., B-506S, manufactured by Iijima Electronics Co., Ltd.) in the case of oxygen remaining in a solvent, and by calculation from the number of moles of oxygen atoms in the solvent in the case of oxygen-containing solvents.
[0073] The amount of oxygen in the oxygen source is preferably 100 ppm by mass or more, more preferably 1000 ppm by mass or more, and even more preferably 3000 ppm by mass or more, calculated as O 2 based on the weight of the electrolyte.
[0074] Also, there is no problem if it is contained to an extent that does not inhibit the ionic conductivity of the electrolyte, and the amount is preferably 200 mass % or less, more preferably 50 mass % or less, and even more preferably 10 mass % or less, based on the weight of the electrolyte, calculated as O2.
[0075] Thus, the method for producing the powder of the present invention preferably includes a step of pulverizing a sulfide-based solid electrolyte containing at least one of a crystalline phase and an amorphous phase in the presence of a chromium source and an oxygen source.
[0076] In the case of the wet grinding method, the type of solvent used is not particularly limited, but since the sulfide-based solid electrolyte has a property of easily reacting with moisture and deteriorating, it is preferable to use a non-aqueous organic solvent.
[0077] The type of non-aqueous organic solvent is not particularly limited, and examples thereof include hydrocarbon solvents, organic solvents containing a hydroxy group, organic solvents containing an ether group, organic solvents containing a carbonyl group, organic solvents containing an ester group, organic solvents containing an amino group, organic solvents containing a formyl group, organic solvents containing a carboxy group, organic solvents containing an amide group, organic solvents containing a benzene ring, organic solvents containing a mercapto group, organic solvents containing a thioether group, organic solvents containing a thioester group, organic solvents containing a disulfide group, and alkyl halides.
[0078] Examples of the hydrocarbon solvent include cyclohexane, heptane, octane, and toluene, and from the viewpoint of low saturated water concentration, cyclohexane, heptane, and octane are preferred. From the viewpoint of adjusting the water concentration, it is also preferred to mix these hydrocarbon solvents with toluene, dibutyl ether, or the like to form a mixed solvent.
[0079] In order to prevent the sulfide-based solid electrolyte powder from reacting with water and decreasing the lithium ion conductivity during pulverization of the crystalline or amorphous phase of the sulfide-based solid electrolyte, the water concentration of the non-aqueous organic solvent is preferably low. The water concentration of the non-aqueous organic solvent may be, for example, 170 ppm by mass or less, 150 ppm by mass or less, 120 ppm by mass or less, or 100 ppm by mass or less.
[0080] The wet grinding method may be carried out using a grinding machine such as a ball mill, a planetary ball mill, or a bead mill.
[0081] In the wet grinding, in addition to the above-mentioned solvent, an ether compound, an ester compound or a nitrile compound may be added as an additive (dispersant).
[0082] If the solvent or additives remain in the sulfide-based solid electrolyte powder obtained through wet grinding, a drying step may be performed. Drying conditions may be, for example, a temperature of 100°C or higher and 200°C or lower. The drying time is not particularly limited, and may be, for example, 10 minutes or longer and 24 hours or shorter. The drying step may be performed under reduced pressure, for example, an absolute pressure of 50 kPa or lower. The drying step may be performed using a hot plate, a drying furnace, an electric furnace, or the like.
[0083] In this manufacturing method, the chromium source is added at the powderization stage in step 2, so that Cr is deposited on the particle surface of the powder. 3+ However, in the present invention, Cr is present on the surface of the particles of this powder. 3+ The method of making Cr exist on the particle surface of the powder is not limited to this. 3+ There is no particular limitation as long as the method is such that a chromium source is present on the powder surface by ion exchange or PVD, and then Cr is removed by subsequent treatment. 3+ may be present on the particle surface.
[0084] The present invention is not limited to the above-described embodiments, and various modifications can be adopted within the scope of the present invention. For example, the present invention is not limited to the above-described embodiments, and appropriate modifications and improvements are possible. In addition, the material, shape, size, number, and location of each component in the above-described embodiments are arbitrary as long as they can achieve the present invention, and are not limited.
[0085] As described above, the present specification discloses the following: [1] A sulfide-based solid electrolyte powder that emits photoluminescence light with wavelengths between 660 and 750 nm. [2] The sulfide-based solid electrolyte powder according to [1], which has a photoluminescence peak ratio of 0.2 or more in a Raman spectrum obtained by excitation with light having a wavelength of 532 nm, as shown in the following formula: Photoluminescence peak ratio = Raman shift 4300 cm -1 ~4500cm -1Integrated intensity of peaks in the region / Raman shift 400~450cm -1 Integrated intensity of peaks in the region [3] The sulfide-based solid electrolyte powder according to [1] or [2], which contains argyrodite-type crystals. [4] The sulfide-based solid electrolyte powder according to any one of [1] to [3], which has a lattice distortion of 0.002 or more. [5] The sulfide-based solid electrolyte powder according to any one of [1] to [4], which satisfies the following formula: BET specific surface area (m 2 / g) × lattice distortion ≧ 0.01 [6] The sulfide-based solid electrolyte powder according to any one of [1] to [5], wherein the atomic ratio of Cl element to Br element is 0.2:1.6 to 1.6:0.2. [7] A method for producing the sulfide-based solid electrolyte powder according to any one of [1] to [6]. [8] A method for producing a sulfide-based solid electrolyte powder according to [7], comprising a step of pulverizing a sulfide-based solid electrolyte containing at least one of a crystalline phase and an amorphous phase in the presence of a chromium source and an oxygen source. [9] A sulfide-based solid electrolyte layer comprising the sulfide-based solid electrolyte powder according to any one of [1] to [6].
[10] A lithium ion secondary battery comprising the sulfide-based solid electrolyte powder according to any one of [1] to [6]. EXAMPLES
[0086] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto. Examples 1 to 6, 8, and 9 are examples, and Examples 7 and 10 are comparative examples.
[0087] (BET specific surface area) The sulfide-based solid electrolyte powder obtained in each example was measured by the krypton adsorption BET multipoint method using a specific surface area and pore distribution measurement device (Micromeritics, ASAP-2020 pore distribution measurement device) to determine the specific surface area. The measurements, including sampling and measurement, were performed without contacting the material with the air. Specifically, as a pretreatment, the pressure was reduced at room temperature for 12 hours or more. The sample weight was 0.15 g, and measurements were performed at 5 or more points in the range of relative pressure (P / P0) of 0.1 to 0.25 at an analysis temperature of -196°C, and a BET plot was created. The specific surface area was calculated from the obtained plot. The results are shown in Table 1, “BET specific surface area (m 2 / g)" item.
[0088] (Photoluminescence evaluation) For the sulfide-based solid electrolyte powder obtained in each example, a Raman spectrum was obtained using a Raman spectrometer (Horiba, LabRAM HR Evolution) with 532 nm wavelength light as excitation light, an objective lens with a magnification of 10 and a numerical aperture of 0.25, and the power of the laser focused on the sulfide-based solid electrolyte powder was adjusted to about 5 mW. The sulfide-based solid electrolyte powder was sealed in a synthetic quartz glass cell in a glove box with a dew point controlled to below -60°C, and the measurement was performed while preventing exposure to the atmosphere. The Raman spectrum was intensity calibrated using a standard halogen lamp light source. The Raman spectrum obtained had a Raman shift of 4300 cm -1 ~4500cm -1 The integrated intensity of the peak in the region and the Raman shift of 400-450 cm -1 The integrated intensity of the peak in this region was calculated, and the photoluminescence peak ratio was calculated using the following formula: The integrated intensity of the peak was evaluated by calculating the integrated area of the region enclosed by the spectrum and the baseline, using the straight line connecting both ends of the peak as the baseline, as shown in Figures 1 and 2. Photoluminescence peak ratio = Raman shift 4300 cm -1 ~4500cm -1 Integrated intensity of peaks in the region / Raman shift 400~450cm -1 Integrated intensity of peaks in the region For Examples 1, 3, and 7 described below, the results of Raman spectra are shown in FIG.
[0089] (Reaction current evaluation (electrochemical stability evaluation)) <Preparation of Carbon> The electronic conductive component of the working electrode composite has a surface area of 62 m2 by the BET method. 2 The carbon black samples used were: (1) C65 dried in a Buchi oven at 300 °C for 24 h, and (2) C65 treated in a H2 / Ar reducing stream (20 vol% H in Ar) at 800 °C for 12 h.
[0090] <Cyclic voltammetry> First, 60 mg of the sulfide-based solid electrolyte powder obtained in Examples 1 to 10 was filled into a PEEK housing and manually compressed with a stainless steel stamp. The solid electrolyte-carbon electrode composite was prepared by mixing the solid electrolyte and carbon in a weight ratio of 9:1 and manually grinding them in an agate mortar for 15 minutes. A mass of 12 mg of the solid electrolyte-carbon composite was placed on a solid electrolyte pellet to prepare a working electrode. This sample was uniaxially pressed at 35 kN (pressure 440 MPa) for 3 minutes. After adding a 100 μm thick indium foil (ChemPur, 99.999%) with a diameter of 9 mm as a counter electrode to the opposite side of the pellet, the cell was fixed to an aluminum frame with a torque of 10 Nm to generate a pressure of about 60 MPa. Indium metal was selected as the material for the counter electrode and reference electrode. When about 1 at% Li was incorporated into indium, the voltage drop was 0.62 V vs Li + A stable open circuit voltage (OCV) of 1000µA / Li was established. After assembly, each cell was allowed to equilibrate for 1 hour. The CV experiment was performed using a VMP300 potentiostat (Biologic) at a temperature of 298 K, a scan rate of 0.1 mV / s, and a high potential sweep from the OCV to the high potential side in the range of 1.9 to 4.0 V. The current value (mA) at 4.0 V vs. In / InLi was calculated as the particle specific surface area (m 2 The reaction current value was calculated by dividing the reaction current by the molecular weight (Mg) and compared between the samples.
[0091] (30min H2S generation (water resistance evaluation)) The amount of hydrogen sulfide generated was measured in an environment with a dew point of -20°C (gas flow rate 0.5 L / min, 10 mg of sample placed). The amount of H2S generated in 30 minutes (ml / g of sample) was calculated based on the BET specific surface area (m 2 / g) to obtain the mass of 1 m of sample. 2 The amount of H2S generated per ml was calculated. 2 According to this index, a smaller value indicates that the generation of H2S from the surface is suppressed, i.e., the sample has better water resistance.
[0092] (Lattice distortion (XRD)) For each sulfide-based solid electrolyte, synchrotron radiation X-ray diffraction measurements were performed, and the crystal structure was refined by the Rietveld method using RIETAN-FP (version: 3.12) software. Rietveld analysis was performed, and the structure with the lowest Rwp value was determined to be the crystal structure of each example. The Rwp value is the reliability factor Rwp (R-weighted pattern), which is a general guideline for the entire analysis range in fitting structure refinement by Rietveld analysis. The lower the Rwp value, the better, and in this analysis, the lowest Rwp value was less than 10%. The lattice distortion was calculated by applying the peak position (2θ) and the half-width (β) of each peak obtained from the Rietveld analysis to the Williamson-Hall plot. The synchrotron radiation X-ray diffraction measurements were performed by packing the sample into a glass capillary and performing the measurements in an environment that was not exposed to the atmosphere, including during sample handling and measurement.
[0093] (Preparation of sulfide-based solid electrolyte powder) Examples 1-3 Lithium sulfide powder (Sigma, purity 99.98%), diphosphorus pentasulfide powder (Sigma, purity 99%), lithium chloride powder (Sigma, purity 99.99%), and lithium bromide powder (Sigma, purity 99.995%) were weighed out in a dry nitrogen atmosphere to obtain the composition shown in Table 1, placed in a quartz test tube, and vacuum sealed. The mixture was melted at 750°C for 1 hour and then cooled to obtain a sample. The obtained sample was crushed in a mortar, mixed with 0.1 wt% Cr2O3, and pulverized. For pulverization, 2 g of electrolyte powder containing 0.1 wt% Cr2O3, 4 g of heptane, and 4 g of dibutyl ether were added, and an alumina ball of Φ1 mm was added, and wet pulverization was performed for a predetermined time shown in Table 1. After that, the mixture was dried at 180°C for 3 hours to obtain sulfide-based solid electrolyte powders of Examples 1 to 3.
[0094] Example 4 First, a sample before pulverization was obtained in the same manner as in Example 1. The obtained sample was crushed in a mortar, mixed with 0.01 wt% Cr2O3, and pulverized. The pulverization was carried out by adding 2 g of electrolyte powder containing 0.01 wt% Cr2O3, 4 g of heptane, 4 g of dibutyl ether, and a Φ1 mm alumina ball, and wet pulverization was carried out for 90 minutes. The pulverization media was then changed from 1 mm to 0.3 mm, and pulverization was continued for 90 minutes, after which the mixture was dried at 180°C for 3 hours to obtain the sulfide-based solid electrolyte powder of Example 4.
[0095] Example 5 First, a sample before pulverization was obtained in the same manner as in Example 1. The obtained sample was crushed in a mortar, mixed with 0.1 wt% Cr2O3, and pulverized. For pulverization, 2 g of electrolyte powder containing 0.1 wt% Cr2O3, 8 g of heptane (water content ≦5 wt ppm), and an alumina Φ1 mm ball were added, and wet pulverization was performed for 90 minutes. After that, the mixture was dried at 180°C for 3 hours to obtain the sulfide-based solid electrolyte powder of Example 5.
[0096] Example 6 The raw materials were mixed to obtain the composition shown in Table 1, and an amorphous sample was obtained by mechanical milling using a planetary ball mill (D 50 2 g of the sample was placed in a rotary kiln and reacted at 385°C for 5 hours while stirring the sample at 10 rpm to obtain argyrodite crystals (D 50The powder was pulverized by adding 2 g of electrolyte powder containing 0.1 wt% Cr2O3, 4 g of heptane, and 4 g of dibutyl ether, and then adding an alumina ball having a diameter of 1 mm. The powder was pulverized at a rotation speed of 50 rpm for 90 minutes to obtain a sulfide-based solid electrolyte powder of Example 6. 50 is the particle diameter D 50 This refers to the particle size distribution at which 50 volume % of the particles have a particle size equal to or less than this value when measured using a particle size distribution analyzer using the laser diffraction method (Microtrac's laser diffraction particle size distribution analyzer MT3300EXII).
[0097] Example 7 First, a sample before pulverization was obtained in the same manner as in Example 1. Electrolyte powders containing 0.1 wt% Cr2O3 were mixed without being pulverized, and these were mixed in a mortar to obtain a sulfide-based solid electrolyte powder of Example 7.
[0098] Example 8, Example 9 The raw materials were weighed out to obtain the composition shown in Table 1, placed in a quartz test tube, and vacuum sealed. After melting at 750°C for 1 hour, the sealed tube was quenched in water to obtain a sulfide glass sample. The obtained sample was crushed in a mortar, mixed with 0.1 wt% Cr2O3, and pulverized. For pulverization, 2 g of electrolyte powder containing 0.1 wt% Cr2O3, 4 g of heptane, and 4 g of dibutyl ether were added, and an alumina Φ1 mm ball was placed in the mixture, and wet pulverization was performed for the specified time shown in Table 1. The mixture was then dried at 180°C for 3 hours and heat-treated at 250°C to obtain Li7P3S. 11 As a result, sulfide-based solid electrolyte powders having the above-mentioned crystal structure of Examples 8 and 9 were obtained.
[0099] Example 10 The raw materials were weighed and mixed to obtain the composition shown in Table 1, and an amorphous sample was obtained by mechanical milling using a planetary ball mill (D 50 2 g of the sample was placed in a rotary kiln and reacted at 260°C for 1 hour while stirring at 10 rpm to obtain Li7P3S 11 The crystals obtained were of the type D 50After that, electrolyte powder containing 0.1 wt % Cr2O3 was mixed without being crushed, and these were mixed in a mortar to obtain a sulfide-based solid electrolyte powder of Example 10.
[0100] [Table 1]
[0101] Li in Examples 1-7 5.4 P.S. 4.4 Cl 0.8 Br 0.8 In the sulfide-based solid electrolyte powder of the present invention, it was found that Examples 1 to 6 of the present invention, which emitted photoluminescence light with a wavelength of 660 to 750 nm, had a low reaction current and were excellent in electrochemical stability. In addition, it was found that Examples 1 to 6 of the present invention generated a small amount of H2S and had excellent water resistance. This is because Examples 1 to 6 of the present invention emitted photoluminescence light with a wavelength of 660 to 750 nm and had relatively high lattice distortion, and therefore Cr was formed on the particle surface. 3+ It is believed that the incorporation of improves the electrochemical stability and water resistance.
[0102] On the other hand, Comparative Example 7 showed a high reaction current and a large amount of H2S generation, and was found to be inferior in electrochemical stability and water resistance. This is because the sample did not emit photoluminescence light in the wavelength range of 660 to 750 nm and had relatively low lattice distortion, and therefore Cr was not formed on the particle surface. 3+ This is believed to be because the electrochemical stability and water resistance were not improved as a result.
[0103] Li7P3S in Examples 8-10 11 In the sulfide-based solid electrolyte powder of the present invention, it was found that Examples 8 and 9 of the present invention, which emitted photoluminescence light with a wavelength of 660 to 750 nm, had a low reaction current and were excellent in electrochemical stability. It was also found that Examples 8 and 9 of the present invention generated a small amount of H2S and were excellent in water resistance. This is because Examples 8 and 9 of the present invention emitted photoluminescence light with a wavelength of 660 to 750 nm, and therefore Cr was deposited on the particle surface.3+ It is believed that the incorporation of improves the electrochemical stability and water resistance.
[0104] On the other hand, Comparative Example 10 showed a high reaction current and a large amount of H2S generation, and was found to be inferior in electrochemical stability and water resistance. This is because the sample did not emit photoluminescence light in the wavelength range of 660 to 750 nm and had relatively low lattice distortion, and therefore Cr was not formed on the particle surface. 3+ This is believed to be because the electrochemical stability and water resistance were not improved as a result.
[0105] Although various embodiments have been described above with reference to the drawings, it goes without saying that the present invention is not limited to such examples. It is clear that a person skilled in the art can come up with various modified or revised examples within the scope of the claims, and it is understood that these also naturally belong to the technical scope of the present invention. Furthermore, the components in the above-mentioned embodiments may be arbitrarily combined within the scope of the invention.
[0106] This application is based on a Japanese patent application (Patent Application No. 2022-098230) filed on June 17, 2022, the contents of which are incorporated by reference into this application.
Claims
1. A sulfide-based solid electrolyte powder that emits photoluminescence light with a wavelength between 660 and 750 nm, and has a photoluminescence peak ratio of 0.03 or more in a Raman spectrum obtained by excitation with light having a wavelength of 532 nm, as shown in the following formula: Photoluminescence peak ratio = Raman shift 4300 cm -1 ~4500cm -1 Integrated intensity of peaks in the region / Raman shift 400-450 cm -1 Integrated intensity of peaks in the region
2. The sulfide-based solid electrolyte powder according to claim 1 , comprising argyrodite-type crystals.
3. The sulfide-based solid electrolyte powder according to claim 1, having a lattice distortion of 0.002 or more.
4. The sulfide-based solid electrolyte powder according to claim 1 , which satisfies the following formula: BET specific surface area (m 2 / g) × lattice distortion ≧ 0.01
5. The sulfide-based solid electrolyte powder according to claim 1, wherein the atomic ratio of Cl element to Br element is 0.2:1.6 to 1.6:0.
2.
6. The sulfide-based solid electrolyte powder according to claim 1 , which is a crystallized glass.
7. The crystallized glass is Li-P-S-Ha-based crystallized glass (Ha represents at least one element selected from halogen elements) or Li-P-S element-containing crystallized glass. The sulfide-based solid electrolyte powder according to claim 6.
8. The method for producing the sulfide-based solid electrolyte powder according to any one of claims 1 to 7.
9. 9. A method for producing a sulfide-based solid electrolyte powder according to claim 8, comprising the step of pulverizing a sulfide-based solid electrolyte containing at least one of a crystalline phase and an amorphous phase in the presence of a chromium source and an oxygen source.
10. A sulfide-based solid electrolyte layer comprising the sulfide-based solid electrolyte powder according to any one of claims 1 to 7.
11. A lithium ion secondary battery comprising the sulfide-based solid electrolyte powder according to any one of claims 1 to 7.
Citation Information
Patent Citations
Sulfide solid electrolyte material
JP2011044249A
Inorganic solid electrolyte, and lithium secondary battery
JP2012190553A
Positive electrode for all-solid battery, and all-solid battery including the positive electrode
JP2013084496A
Electrode for all-solid battery, and all-solid battery including the same
JP2013097969A
Sulfide-based solid electrolyte for lithium ion batteries
JP2016024874A